Pengaruh Work-Life Balance, Kompensasi, Kepuasan Kerja, dan Motivasi Terhadap Kinerja Karyawan UMKM di Kepulauan Seribu - Faiz Khaldun; Wiwin; Muhaimin; Eka Sutisna; M. Gelar Faisal (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the influence of work-life balance, compensation, job satisfaction, and motivation on the performance of MSME employees in the Seribu Islands. This study uses a quantitative approach with explanatory research. Data were collected by distributing questionnaires to MSME employees working in the culinary, trade, tourism, lodging, and local creative business sectors in the Seribu Islands. The sampling technique used purposive sampling, while data analysis was conducted through validity tests, reliability tests, classical assumption tests, multiple linear regression, partial tests, simultaneous tests, and coefficients of determination. The results show that work-life balance, compensation, job satisfaction, and motivation have a positive effect on employee performance. Partially, compensation and motivation are the dominant factors in driving performance improvement, while work-life balance and job satisfaction strengthen employee psychological stability, loyalty, and work responsibility. Simultaneously, these four variables are proven to be able to explain variations in MSME employee performance strongly. This finding confirms that improving MSME employee performance is not only determined by financial aspects, but also by work-life balance, emotional satisfaction, and internal drive to work productively.